Evaluating the effect of delayed activation of rapid response teams on patient outcomes: a systematic review protocol - Michael K. Xu (Systematic Reviews, 2018)
Abstract Background Rapid response teams have been widely adopted across the world. Although evidence for their efficacy is not clear, they remain a popular means to detect and react to patient deterioration. This may in part be due to there being no standardized approach to their usage or implementation. A key component of their ability to be effective is the speed of response. Objective The objective of this review is to evaluate the effect of delayed response by rapid response teams on hospital mortality (primary), cardiac arrest, and intensive care transfer rates (secondary). Methods This review will include randomized and non-randomized studies which examined the effect of delayed response times by rapid response teams on patient mortality, cardiac arrest, and intensive care unit admission rates. This review will include studies of adult patients who have experienced a rapid response team consultation. The search strategy will utilize a combination of keywords and MeSH terms. MEDLINE and Embase will be searched, as well as examining gray literature. Two reviewers will independently screen retrieved citations to determine if they meet inclusion criteria. Studies will be selected that provide information about the impact of response time on patient outcomes. Comparisons will be made between consults that arrive in a timely manner and consults that are delayed. Quality assessment of randomized studies will be conducted in accordance with guidelines from the Cochrane Handbook for Systematic Reviews of Interventions. Quality assessment of non-randomized studies will be based on the Risk of Bias in Non-randomized Studies-of Interventions (ROBINS-I) assessment tool. Results of the review will be reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Discussion This systematic review will identify and synthesize evidence around the impact of delayed response by rapid response teams on patient mortality, cardiac arrest, and intensive care transfer rates. Systematic review registration PROSPERO Registration: CRD42017071842.